Zombies Never Die: The Double Life Bub1 Lives in Mitosis - Zhang, Yuqing; Song, Chunlin; Wang, Lei; Jiang, Hongfei; Zhai, Yujing; Wang, Ying; Fang, Jing; Zhang, Gang (Frontiers in Cell and Developmental Biology, 2022)
When eukaryotic cells enter mitosis, dispersed chromosomes move to the cell center along microtubules to form a metaphase plate which facilitates the accurate chromosome segregation. Meanwhile, kinetochores not stably attached by microtubules activate the spindle assembly checkpoint and generate a wait signal to delay the initiation of anaphase. These events are highly coordinated. Disruption of the coordination will cause severe problems like chromosome gain or loss. Bub1, a conserved serine/threonine kinase, plays important roles in mitosis. After extensive studies in the last three decades, the role of Bub1 on checkpoint has achieved a comprehensive understanding; its role on chromosome alignment also starts to emerge. In this review, we summarize the latest development of Bub1 on supporting the two mitotic events. The essentiality of Bub1 in higher eukaryotic cells is also discussed. At the end, some undissolved questions are raised for future study.